2016
DOI: 10.1117/1.jbo.21.7.077001
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of optical properties using interstitial cylindrical diffusers as source and detector fibers

Abstract: Abstract. We demonstrate recovery of optical properties using arrays of interstitial cylindrical diffusing fibers as sources and detectors. A single 1-cm diffuser delivered laser illumination at 665 nm, while seven 1-and 2-cm diffusers at 1-cm grid spacing acted as detectors. Extraction of optical properties from these measurements was based upon a diffusion model of emission and detection distributions for these diffuser fibers, informed by previous measurements of heterogeneous axial detection. Verification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…On the other hand, cylindrical diffusers allow for using fewer optical fibers to cover the same treatment volume, and it has been recently shown that cylindrical diffusers can be used to evaluate the optical properties. 113,114 The measurements can be done in continuous wave (CW) mode or using pulsed (∼ps short pulses) or frequency-modulated (∼100 MHz) light. Generally, modulated measurements may provide more information, which can give more accurate predictions, but the technology is more complicated and costly.…”
Section: Integration Of Dosimetry In Ipdtmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, cylindrical diffusers allow for using fewer optical fibers to cover the same treatment volume, and it has been recently shown that cylindrical diffusers can be used to evaluate the optical properties. 113,114 The measurements can be done in continuous wave (CW) mode or using pulsed (∼ps short pulses) or frequency-modulated (∼100 MHz) light. Generally, modulated measurements may provide more information, which can give more accurate predictions, but the technology is more complicated and costly.…”
Section: Integration Of Dosimetry In Ipdtmentioning
confidence: 99%
“…On the other hand, cylindrical diffusers allow for using fewer optical fibers to cover the same treatment volume, and it has been recently shown that cylindrical diffusers can be used to evaluate the optical properties. 113 , 114 …”
Section: Integration Of Dosimetry In Ipdtmentioning
confidence: 99%